Siderite/Concrete catalysts for H2-enriched gas production from biomass steam gasification. (1st March 2022) - Ruivo, Luís; Oliveira, Hortência; Gomes, Helena; Cruz, Nuno; Yaremchenko, Aleksey; Tarelho, Luís A.C.; Frade, Jorge
Highlights: Concrete/siderite-based catalysts are demonstrated for H2 promotion in gasification. Activity was affected by temperature (43%), concrete ratio (30%) and steam (27%). 50%concrete/siderite exhibited high activity for the water gas shift reaction. Carbon conversion (54 to 59%) and cold gas efficiency (55 to 61%) increased. H2 production increased from 34 to 49 g H 2 ∙ k g d r y, f u e l - 1 during steam gasification. Abstract: In this study, granulated siderite/concrete-based catalysts are proposed for in-situ applications in biomass steam gasification, seeking H2 -enrichement by the contribution of water gas shift and CO2 adsorption. A cost-effective procedure has been applied for the preparation of granulated catalysts. Water Gas Shift reaction was studied in a fixed bed reactor and Taguchi experimental design was used to elucidate the relevance of experimental parameters on catalyst performance. The results show that the impact of reaction temperature, concrete/siderite ratio and steam to carbon molar ratio on H2 promotion had the following order: reaction temperature (43.1%), concrete/siderite ratio (30.2%) and steam to carbon molar ratio (26.7%). Additionally, the catalyst exhibited high activity when integrated into the freeboard zone of a bubbling fluidized bed gasifier. Compared to the reference condition, one observed significant impact at 700 °C on the H2 :CO ratio (1.9 to 3.3), H2 production (33.8 to 48.6 g H 2 ∙ k g d r y, f u e l - 1 ), carbon conversion efficiency (54.1 to 58.6%) and cold gas efficiency (55.0 to 60.9%). Though the catalyst exhibited resistance to sintering, post-mortem analysis suggests loss of active species after repeated cycles of regeneration due to thermal-induced stresses, which caused gradual decrease in activity.